Alex Katz - gathering - Brinson, Katherine ca. 20. Jh; Prombaum, Levi ca. 20. Jh; Chuong, Jennifer Y.; Horowitz, David Max; Jafa, Arthur 1960-; Kitamura, Katie M. 1979-; Koestenbaum, Wayne 1958-; Lajer-Burcharth, Ewa ca. 20. Jh; Lotery, Kevin; Peiffer, Prudence (Guggenheim, 2022)
"Across nearly eight decades of intense creative production, Alex Katz has sought to capture a state of "absolute awareness" in paint. Whether evoking a glancing exchange between friends or a shaft of light filtered through trees, he has aimed to create a record of "quick things passing," compressing the flux of everyday life into a condensed burst of optical perception. Published on the occasion of the artist's first US career retrospective in more than 30 years, Alex Katz: Gathering offers a definitive account of Katz's artistic project, demonstrating both its marked coherence and restless evolution. Generously illustrated, the book features the full breadth of the artist's work across mediums and formats, from intimate sketches of riders on the New York City subway in the late 1940s to the rapturous, monumentally scaled landscapes that have dominated his recent production. Essays by artists, writers and art historians offer fresh, authoritative overviews of the artist's practice alongside more focused considerations of specific facets of his art, including his flower paintings, collages, prints, freestanding "cutouts" and set design collaborations with the Paul Taylor Dance Company. A sourcebook of historical reviews, essays and poems rounds out the volume, which offers an overdue reassessment of the artist's oeuvre"--
Impressum: Published on the occasion of the exhibition "Alex Katz: Gathering", Solomon R. Guggenheim Museum, New York, October 21, 2022 - February 20, 2023
Keywords: Katz, Alex -- 1927-; Katz, Alex / 1927- / Exhibitions; ART / General; Katz, Alex / 1927-; Exhibition catalogs; Ausstellungskatalog -- Solomon R. Guggenheim Museum -- 21.10.2022-20.02.2023 -- New York, NY; Bildband